Long‐term outcomes following transatrial versus transventricular repair on right ventricular function in tetralogy of Fallot. Issue 11 (16th November 2017) - Padalino, Massimo A.; Cavalli, Giacomo; Albanese, Sonia B.; Pace Napoleone, Carlo; Guariento, Alvise; Cascarano, Maria Teresa; Perazzolo Marra, Martina; Vida, Vladimiro; Boccuzzo, Giovanna; Stellin, Giovanni
Abstract: Background and Aim of the Study: Outcomes after repair of tetralogy of Fallot (TOF) are good with either a transventricular (TV) or transatrial (TA) approach. We sought to determine if there is a relationship between the TV or TA approach and right ventricular (RV) function, and the role of residual pulmonary regurgitation (PR) on the long‐term outcomes. Methods: This was a retrospective cohort multicentric study on survivors after surgical repair of TOF (TA versus TV approach, ±transannular patch) between 1990 and 2004. All patients underwent magnetic resonance imaging to assess RV volume, function, and PR. Patients were matched for length of follow‐up and age. Clinical adverse events were retrieved from institutional databases. Results: Seventy‐nine patients (TA/TV = 37/42, median age 0.3 and 1.0 yrs, respectively) were included. At a median follow‐up of 16.6 years (12.5‐20.3), there were no differences in freedom from reintervention (either catheter or surgical), RV volumes, function, and PR between the TA and TV groups. Pulmonary valve (PV) replacement was significantly less frequent in the TA subgroup ( P  = 0.033) and patients with a preserved PV showed significantly lower RV volumes and less adverse events at follow‐up. Conclusions: There is no significant difference in RV volumes and function between the TA and TV. However, the TA approach seems to be protective against PV replacement in the long‐term. When PV is not preserved at repair, residual pulmonary regurgitation is a significant cause of late RV dysfunction and dilation, and is associated with a higher rate of late adverse events.